Produksi Biofuel dari Minyak Nyamplung Menggunakan Reaksi Hydrocracking - Al-Muttaqii, Muhammad; Rinaldi, Nino; Irawan, Chairul (Lambung Mangkurat University Press, 2024)
Studies on hydrocracking of nyamplung oil into biofuel have been studied using the HZSM-5 catalyst. The HZSM-5 catalyst was modified into HZSM-5 mesopore and impregnated using transition metals namely Cobalt, Nickel and Cuprum with a metal loading of 5% and a metal ratio ratio of 1:1:1. The resulting catalyst was then characterized using X-Ray Difraction (XRD), Brunauer Emmet Teller (BET), and Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX). The hydrocracking process was carried out in a batch reactor by adding 0.5 grams of catalyst and a volume of Nyamplung oil of 15 mL. The temperaturs used vary from 250, 300, and 350 oC with a hydrogen gas pressure of 20 bar, and a reaction time of 2 hours. The resulting biofuel product is analyzed using Gas Chromatography Mass Spectrometry (GC-MS). The resulting biofuel product has a compound composition of n-paraffin with an area % of 26.72%, cycloparaffin 3.34%, olefin 0.33%, aromatic compounds 15.83% and polycyclic aromatics 12.56%, with a conversion of 72.1% in temperatur 350 oC. Biofuel from nyamplung oil can be used as an alternative fuel to reduce dependence on fossil fuels through the hydrocracking process.